Effectiveness of psychological rehabilitation, using Dohsa-Hou, on hemodialysis patients’ depression, anxiety, and stress in Zahdan city - Mahmoud Shirazi (Journal of Birjand University of Medical Sciences, 2016)
Background and Aim: Dialysis patients are prone to various complications such as physical, economic, social and psychological problems which can result in psychopathological complications.. The current study aimed at assessing the effectiveness of psychological rehabilitation using Dohsa-Hou, on reducing ESRD (Hemodialysis) patients’ depression, anxiety, and stress, in Zahdan city.